Étude longitudinale des relations entre la perception de compétence, la motivation et le rendement scolaires - Lebeau, Rose; Bouffard, Thérèse (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Although several theories suggest that the perception of competence plays a central role in motivation and academic performance, there is no consensus on the direction of their relationship. This longitudinal study covering the primary-secondary transition examines this question. From the 5th year of primary school and once a year during the following 4 years, 830 pupils answered a questionnaire on their perception of competence and their motivation. Their performance was reported by their teachers. Controlling for the effect of pupils’ gender and mental abilities and parental education, the results indicate a bidirectional association between perceived competence and performance. The perception of competence systematically predicts motivation, but not the reverse. There is little relationship between motivation and performance. The discussion emphasizes the importance of developing a positive perception of competence in school functioning.